Modern Techniques for Cervical Cancer Radiotherapy - P. A. Lushnikova; E. S. Sukhikh; P. V. Izhevsky; Ya. N. Sutygina; M. A. Tatarchenko; I. B. Pyzhova (Креативная хирургия и онкология)
Cervical cancer is a socially significant illness often impacting women of reproductive and working age. The patients’ young age and social activity warrant the development of effective and safe therapies.The past decades have witnessed the novel radiation techniques to contain cervical cancer: 3DCRT-3D, IMRT, and VMAT, adaptive radiotherapy, CT/MRI-guided intracavitary radiation, combined interstitial and intracavitary radiation, abandoning intracavitary intervention for external beam delivery with sequential or concurrent cervical dose escalation, under brachytherapy unfeasible.Modern equipment and treatment planning systems allow a high dose delivery to the tumour and intracavitary treatment with visual control of the target and organs at risk. Combining of intracavitary and interstitial radiotherapy enables a better dose coverage of the target at a minimal radiation impact on organs at risk.Phasing-out of intracavitary for external radiotherapy may enable a cancericide dose delivery to the tumour under intractable intracavitary treatment.The major goal of technic novelties is the establishment of personalised radiotherapy for improving treatment outcomes and reducing the incidence and/or severity of radiation side effects. The article overviews the radiotherapy techniques for cervical cancer treatment and routes of their development.